Dual-energy X-ray absorptiometry and fracture prediction in patients with spinal cord injuries and disorders. Issue 3 (March 2017) - Abderhalden, L.; Weaver, F.; Bethel, M.; Demirtas, H.; Burns, S.; Svircev, J.; Hoenig, H.; Lyles, K.; Miskevics, S.; Carbone, L.
Abstract Summary Low T-scores at the hip predict incident fractures in persons with a SCI. Introduction Persons with a spinal cord injury (SCI) have substantial morbidity and mortality following osteoporotic fractures. The objective of this study was to determine whether dual-energy X-ray absorptiometry (DXA) measurements predict osteoporotic fractures in this population. Methods A retrospective historical analysis that includes patients (n = 552) with a SCI of at least 2 years duration who had a DXA performed and were in the VA Spinal Cord Disorders Registry from fiscal year (FY) 2002–2012 was performed. Results The majority of persons (n = 455, 82%) had a diagnosis of osteoporosis or osteopenia, with almost half having osteoporosis. BMD and T-scores at the lumbar spine were not significantly associated with osteoporotic fractures (p > 0.48) for both. In multivariable analyses, osteopenia (OR = 4.75 95% CI 1.23–17.64) or osteoporosis (OR = 4.31, 95% CI 1.15–16.23) compared with normal BMD was significantly associated with fractures and higher T-scores at the hip were inversely associated with fractures (OR 0.73 (95% CI 0.57–0.92)). There was no significant association of T-scores or World Health Organization (WHO) classification with incident fractures in those with complete SCI (p > 0.15 for both). Conclusion The majority (over 80%) of individuals with a SCI have osteopenia or osteoporosis. DXA-derived measurements at the hip, but not the lumbar spine, predict fracture risk in persons with a SCI. WHO-derived bone density categories may be useful in classifying fracture risk in persons with a SCI.